2017
DOI: 10.1016/j.ijrobp.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Music Therapy on Anxiety in Cancer Patients Undergoing Simulation for Radiation Therapy

Abstract: MT significantly lowered patient anxiety and distress during the simulation procedure on the basis of the STAI-S questionnaire and SDT. Incorporating culturally centered individualized MT may be an effective intervention to reduce stressors. Continued research defining the role of MT intervention in improving the patient experience by reducing anxiety is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
26

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 27 publications
2
46
0
26
Order By: Relevance
“…In all three categories, exclusion of studies after sensitivity analysis led to smaller but still significant effect sizes. With regard to psychological well-being and physical symptom distress, the excluded studies were highly influential but also relevant because they had large sample sizes in comparison to the other studies (Gutgsell et al, 2013;Dóro et al, 2017;Rossetti et al, 2017). Regarding quality of life, the identified highly influential study was the only non-randomized controlled trial (Domingo et al, 2015) and therefore likely to be biased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In all three categories, exclusion of studies after sensitivity analysis led to smaller but still significant effect sizes. With regard to psychological well-being and physical symptom distress, the excluded studies were highly influential but also relevant because they had large sample sizes in comparison to the other studies (Gutgsell et al, 2013;Dóro et al, 2017;Rossetti et al, 2017). Regarding quality of life, the identified highly influential study was the only non-randomized controlled trial (Domingo et al, 2015) and therefore likely to be biased.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies assessed the effects of music therapy in the course of radiation therapy and found reductions in anxiety and distress (Rossetti et al, 2017) as well as improvements regarding quality of life, fatigue, and depression (Alcântara-Silva et al, 2018). Both interventions consisted of listening to music (with a therapist) before or during radiation therapy.…”
Section: Music Therapy During Chemotherapy and Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of music therapy in a pediatric oncology hospital was appointed was a family rapprochement facilitator in the context of coping with the disease, thanks to the distraction from the cause of anxiety promoted by the intervention 31 . Amongst the articles that describe anxiety reducing, a North American randomized clinical trial including patients submitted to STAI-S (State-Trait Anxiety Inventory to State Anxiety) questionnaire before and after exposition to radiotherapy and music therapy affirms significant reduction on anxiety and stress levels in the group submitted to music therapy compared to control group 4 . Another North American article described reduction of both anxiety levels and time of hospitalization between patients who underwent breast cancer surgery and were exposed to live music and recorded music before and after the procedure, respectively.…”
Section: Reduction Of Anxietymentioning
confidence: 99%
“…A música, enquanto promotora de saúde, torna-se um recurso importante, que necessita de interação e convívio entre as pessoas. Portanto, essa estratégia musical é eficaz na disseminação de momentos de felicidade, divertimento e integração, sendo capaz de acrescer ao trabalho em equipe (17) . Assim, a equipe do programa de extensão tem vivenciado experiências enriquecedoras no espaço hospitalar, pois, apesar de serem diferentes pessoas, fica evidente que a música transmite paz e esperança aos pacientes de diversas culturas, podendo também levar assistência aos seus familiares/acompanhantes.…”
Section: Síntese Dos Dadosunclassified